IMPACT OF KNOWLEDGE MANAGEMENT PILLARS IN ESTABLISHING KNOWLEDGE REPOSITORIES THROUGH THE MODERATING ROLE OF KNOWLEDGE LEAKAGE: AN APPLIED STUDY IN THE MINISTRY OF IRAQI PLANNİNG (American Journal of Research in Humanities and Social Sciences, 2024)
Purpose - The leakage of knowledge assets, such as intellectual property amassed as a result of information leakage, poses a serious threat to businesses since knowledge is a critical strategic organizational asset that needs to be safeguarded as a competitive resource. organizational skills. The purpose of this paper is to ascertain how knowledge management pillars affect organizational knowledge repositories and how this relationship is established. The study assesses the moderating role of knowledge leaking in the relationship.Design/methodology/approaches - The research employed survey methodologies and quantitative design as a research strategy for gathering data and evaluating the models. The proposed linkages are based on data gathered from 225 employees in the Ministry of Planning.Findings - The results of the data analysis demonstrated that the modifying variable had a detrimental influence on the study model. It was positive except for the interaction between information repositories and the pillars of knowledge management. Many recommendations for additional research were made, and theoretic and practical consequences were explored.Originality/Value - The study aimed to identify knowledge repositories and knowledge management pillars. In addition, knowledge leakage plays a role in enhancing knowledge repository efforts. Finally, the study was conducted in the context of the Iraqi Ministry of Planning. It is the only study that addresses research factors. As a result, it serves as a valuable resource for scholars and other interested parties in fields related to knowledge management.